STUDI VARIASI SUHU PERMUKAAN TANAH DI WILAYAH JAWA TIMUR MENGGUNAKAN SENTINEL-3 SLSTR - Kurnyawati, Pamella; Handoko, Eko Yuli; Syariz, Muhammad Aldila (Jurnal Penginderaan Jauh Indonesia, 2025)
Land surface temperature plays an important role in maintaining the energy balance. Increases in land surface temperature can have a significant impact on global climate and weather patterns. The Sentinel-3 satellite, as one of the earth monitoring instruments capable of monitoring changes in soil moisture. The method used in this research is the remote sensing method using the Sentinel-3 SLSTR level 2 LST satellite to obtain Land Surface Temperature values. While to analyze the condition of temperature variation is correlation analysis based on (LST), (TCWV) and temperature monitoring from BMKG. This research is located in East Java, Indonesia, which has geographical coordinates at a latitude of about 7°30' - 8°45' LS and longitude of about 112°45' - 114°30' East. East Java, as the eastern part of the island of Java, has diverse environmental characteristics, including various land types and vegetation. The LST in 2021 is at a temperature of 18.676 ° C in December for the highest LST value from 2021 data is June with its LST value of 31.659. Meanwhile, for the year 2022, the lowest temperature value is in February with an LST point value of 18.073 ° C for the highest LST value from 2021 data is June with an LST value of 30.707 ° C. Meanwhile, for the year 2023, the lowest temperature value is in February with an LST point value of 25.542 ° C. The highest LST value from 2021 data is in June with an LST value of 30.707 ° C. With the average LST value for three years at a value of 21.936 °C. The average correlation coefficient obtained from the LST variable with TCWV is 0.487. So that the coefficient value can be classified in a moderate category. Meanwhile, the average correlation between the LST and temperature variables from BMKG as a whole has a correlation coefficient value of 0.740. So that from the average correlation coefficient value it can be classified in the Strong category.